1989
DOI: 10.1073/pnas.86.18.6949
|View full text |Cite
|
Sign up to set email alerts
|

Protection against tobacco mosaic virus in transgenic plants that express tobacco mosaic virus antisense RNA.

Abstract: Transgenic tobacco plants that express RNA sequences complementary to the tobacco mosaic virus (TMV) coat protein (CP) coding sequence with or without the tRNAlike structure at the 3' end of the TMV RNA were produced. Progeny of self-pollinated plants were challenged with TMV to determine their resistance to infection. Plants that expressed RNA sequences complementary to the CP coding region and the 3' untranslated region, including the tRNA-like sequences, were protected from infection by TMV at low levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(28 citation statements)
references
References 17 publications
2
25
0
1
Order By: Relevance
“…However, in each case the antisense RNA strategy was found to be considerably less effective than expression of the coat protein. A similar result was obtained for tobacco plants expressing tobacco mosaic virus antisense RNA (Powell et al, 1989). In this case, plants expressing antisense RNA to the coat protein coding region and the 3' untranslated region were protected from infection by TMV at low levels of inoculum.…”
Section: Inhibition or Virusessupporting
confidence: 67%
“…However, in each case the antisense RNA strategy was found to be considerably less effective than expression of the coat protein. A similar result was obtained for tobacco plants expressing tobacco mosaic virus antisense RNA (Powell et al, 1989). In this case, plants expressing antisense RNA to the coat protein coding region and the 3' untranslated region were protected from infection by TMV at low levels of inoculum.…”
Section: Inhibition or Virusessupporting
confidence: 67%
“…Experiments by Powell et al (1989) using antisense RNAs to inhibit the replication of tobacco mosaic virus revealed that these RNAs were effective only when sequences complementary to the 3' tRNA-like structure were present. Rezaian et al (1988) obtained only weak protection against cucumber mosaic virus (CMV) using sequences complementary to the 5' translational start site of CMV RNA-1, and antisense transcripts directed against the 3' non-coding region that did not include the terminal 135 bases were ineffective.…”
Section: Discussionmentioning
confidence: 99%
“…Ahlquist et al (1984) made use of a hybrid arrest strategy to localize the site of BMV replicase recognition by use of cDNAs complementary to the 3' ends of viral RNAs. Recently there have been a number of attempts to apply the antisense strategy both to gene expression in plants (Delauney et at., 1988;teller et al, 1991) and to interfere with virus replication (Rezaian et al, 1988;Cuozzo et al, 1988;Hemenway et al, 1988;Powell et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…In most cases the predicted phenotype is observed in transformed plants harboring the antisense gene, e.g. virus resistance (Powell et al, 1989), delayed senescence (Picton et al, 1993), and altered partitioning of sugar (Kuipers et al, 1995). However, there are some notable exceptions in which the antisense RNA suppression of gene expression produces unexpected results.…”
Section: Roles For Tobacco Anionic Peroxidase In Lignification and Dementioning
confidence: 99%